2015
DOI: 10.1097/ijg.0000000000000060
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy With Mitomycin-C Versus Trabeculectomy With Amniotic Membrane Transplant

Abstract: AMT exhibits potential as an alternative to MMC in trabeculectomy surgery. Over 24 months of follow-up, the use of AMT with trabeculectomy was safe and effective with an IOP-lowering effect comparable to that achieved with the use of MMC, and a reduced rate of postoperative complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(40 citation statements)
references
References 12 publications
0
38
0
2
Order By: Relevance
“…Importantly, Khairy et al recently published that after 24-months follow-up the use of AMT as adjuvant to trabeculectomy was safe and effective. Surgical outcome with respect to IOP control was comparable to the use of MMC (Khairy and Elsawy, 2014). Hence, AMT exhibits a high potential as an alternative to MMC to improve surgical success after trabeculectomy.…”
Section: Amniotic Membrane Transplantationmentioning
confidence: 81%
“…Importantly, Khairy et al recently published that after 24-months follow-up the use of AMT as adjuvant to trabeculectomy was safe and effective. Surgical outcome with respect to IOP control was comparable to the use of MMC (Khairy and Elsawy, 2014). Hence, AMT exhibits a high potential as an alternative to MMC to improve surgical success after trabeculectomy.…”
Section: Amniotic Membrane Transplantationmentioning
confidence: 81%
“…Eighteen studies, reported in 17 full-text articles and one conference abstract, assessed the use of amniotic membrane compared with trabeculectomy, with or without the use of MMC (Bruno 2008; Cai 2012; Cho 2013; Eliezer 2006; Huang 2007; Ji 2013; Khairy 2015; Li 2010; Liu 2009; Ren 2009; Sheha 2008; Stavrakas 2012; Wang 2008; Wang 2009; Yan 2004; Yang 2004; Zhang 2009; Zheng 2005). Findings from 13 of these studies were published in Chinese and accounted for 647 eyes of 536 participants, more than 70% of all 726 participants in the 18 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 33 studies, 10 specified adequate methods of randomization and we assessed them as being at low risk of bias: three out of five studies for Ex-PRESS (De Jong 2009; Netland 2014; Wagschal 2013), four out of eight studies for Ologen (Cillino 2011; Papaconstantinou 2010; Rosentreter 2014; Senthil 2013), three out of 18 studies for amniotic membrane (Cho 2013; Khairy 2015; Stavrakas 2012). The one study that evaluated E-PTFE did not use a completely random allocation method (medical chart number), so we judged it to be at high risk of bias (Cillino 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…опубликовал результаты 24-месячных наблюдений, согласно которым амниотическая мембрана является эффективным и безопасным дополнением трабекулэк-томии. Исходы хирургии с точки зрения уровня ВГД оказались сопоставимыми с таковыми при использо-вании MMC [49]. Таким образом, амниотическую мем-брану можно рассматривать в качестве потенциальной альтернативы по отношению к применению ММС как средства улучшения исходов трабекулэктомии.…”
Section: трансплантация амниотической мембраныunclassified